New Properties of Photons and Photoelectric Effect (Global Journal of Science Frontier Research, 2023)
The photons has an important property It is electrically neutral but couples with electric charges That is why photons do not interact with each other Since photons are mass less Photons do not interact with each other Because it seems that The interaction between charge particles exist only when they are possesses mass Otherwise there will be no any interaction between them